Perspective Of Gender In The Careers Of Degree In Social Sciences And Geography In Four Public Universities Of Colombia - Patiño Gómez, Zaida Liz; Naranjo Villa, Laura; Serna Felipe, Marggie (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The objective of this article is evaluate the genre focus in teaching geography in the undergraduate programs in Social studies and Geography in four public Colombia universities: Pedagógica Nacional, Pedagógica y Tecnológica de Colombia, del Atlántico y del Valle. This investigation used a qualitative methodology that included literature revision, curricular contents, and the production of monography in this universities. The results show the low incidence of the genre broach in the teaching of geography in College, as contents, literature as reflection and investigation. Also, the genre focus slowly emerges in the monography, although they are not broach directly from geography.